Structural Behavior of Sandwich Panels with External Deep-Profiled and Internal Soft Facing - Zbigniew POZORSKI; Rafał SÓL; Jacek SZAJDA; Jolanta BŁASZCZUK (Engineering Transactions, 2013)
Sandwich panels made of deep-profiled steel facesheet, thick and soft PUR core and thin aluminum facesheet are considered. The structural behavior of the panel in two arrangements is analyzed by the way of real experiments. Three-point bending tests were carried out. The laboratory tests unraveled non-linear characteristics of structural behavior. The local instability of the compressed faces was observed. The real experiments were compared with the results of numerical simulations.